Persuasive Communication in a Healthy Lifestyle Campaign in Pandeglang District (Case Study of Arisan Jamban Program) - Malik, Abdul; Putri, Liza Diniarizky (ijd-demos, 2020)
Since 2007, the Amil Zakat Harapan Duafa Institute (LAZ Harfa) has actively initiated a healthy life movement campaign in the Pandeglang Regency, especially to people who are still practicing open defecation (BABS), due to either the lack of latrines or other factors. â€œJambanâ€ in English means latrine. Using the Community Lead Total Sanitation (CLTS) method, this healthy living campaign is focused on the latrine ownership program through the arisan system. An Arisan is a form of rotating savingsÂ inÂ IndonesianÂ culture. From the results of research using case studies, this healthy living movement campaign has brought significant results. Through a persuasive communication process as part of the approach to the community strategy, the results were obtained that by the end of 2019 as many as 29 assisted villages in 8 sub-districts in Pandeglang District had been free from the practice of open defecation. This fact shows that the persuasive communication carried out in this healthy living campaign is quite effective and brings the expected results.Â Sejak tahun 2007 silam, Lembaga Amil Zakat Harapan Duafa (LAZ Harfa) aktif melakukan inisiasi kampanye gerakan hidup sehat di wilayah Kabupaten Pandeglang, khususnya kepada masyarakat yang masih menjalankan kebiasaan membuang air besar sembarangan (BABS), baik karena ketiadaan jamban ataupun karena faktor lain. Menggunakan metode Community Lead Total Sanitation (CLTS), kampanye hidup sehat ini difokuskan pada program kepemilikan jamban melalui sistem arisan. Dari hasil penelitian dengan menggunakan studi kasus, kampanye gerakan hidup sehat ini telah membawa hasil yang disignifikan. Melalui proses komunikasi persuasif sebagai bagian dari strategi pendekatan kepada masyarakat, diperoleh hasil bahwa hingga akhir 2019 sebanyak 29 desa dampingan di 8 kecamatan di Kabupaten Pandeglang telah terbebas dari kebiasaan BABS. Fakta tersebut menunjukkan bahwa komunikasi persuasif yang dilakukan dalam kampanye hidup sehat ini berjalan cukup efektif dan membawa hasil sebagaimana diharapkan.